First grave on the right - Jones, Darynda (New York : St. Martin's Press, 2011)
Using her ability to see ghosts in her work as a private investigator, Charley Davidson begins experiencing intense sensual dreams about a mysterious entity that has been following her throughout her life.
Keywords: Davidson, Charley -- (Fictitious character) -- Fiction; Women private investigators -- Fiction; Women mediums -- Fiction; Romantic suspense fiction; Occult fiction